(untitled) (Sociologisk Forskning, 2025)
Review essay presenting the works of the sociologist Loïc Wacquant. The text follows Wacquants Busy Louie trajectory from arriving in Chicago - his formation as a sociologist of urbanity and an amateur boxer boxer - to his later works, focusing in particular on his latest book Racial Domination.